2013
DOI: 10.1002/aic.14076
|View full text |Cite
|
Sign up to set email alerts
|

Reducing total annualized cost and CO2 emissions in batch distillation: Dynamics and control

Abstract: In this contribution, the direct vapor recompression approach is introduced in a batch distillation operated at an unsteady state condition. This vapor recompressed batch distillation (VRBD) accompanies an isentropic compressor that runs at a fixed as well as variable speed. Aiming to ensure the optimal use of internal heat source, an open-loop control policy is proposed for the VRBD that adjusts either the overhead vapor splitting or the external heat supply to the reboiler. Again, the variable speed VRBD add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results showed that reductions in energy consumption and CO 2 emissions could be achieved [24]. Babu and Jana introduced a direct vapor recompression approach in a batch distillation operated under an unsteady-state condition and achieved significant improvement in thermodynamic efficiency and environmental impact [25]. Gadalla et al studied CO 2 emissions of a heat-integrated distillation column (HIDiC).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that reductions in energy consumption and CO 2 emissions could be achieved [24]. Babu and Jana introduced a direct vapor recompression approach in a batch distillation operated under an unsteady-state condition and achieved significant improvement in thermodynamic efficiency and environmental impact [25]. Gadalla et al studied CO 2 emissions of a heat-integrated distillation column (HIDiC).…”
Section: Introductionmentioning
confidence: 99%